Cationic lipid-assisted nanoparticles for simultaneous delivery of CD47 siRNA and R848 to promote antitumor immune responses - Li, Simin; Chen, Yichang; Ma, Ruolin; Du, Ye; Han, Bing (Frontiers in Pharmacology, 2023)
Introduction: Triple-negative breast cancer (TNBC) usually has a poor prognosis. Although the immunotherapy of TNBC has achieved great progress, only a few patients can benefit from the current treatment. CD47 is widely expressed on the surface of TNBC cells and may become an immune checkpoint for TNBC treatment. Nevertheless, increasingly more attention has been paid to systemic side effects since the ubiquitous expression of CD47 on normal cells. The toll-like receptor (TLR) agonist resiquimod (R848) can activate dendritic cells (DCs) and promote the maturation of immune cells in the tumor microenvironment, which further enhances the tumor inhibition ability of the immune system and synergizes with CD47 small interfering RNA (siRNA) for TNBC therapy. However, ideal delivery platforms such as nanocarriers are still needed because its weakness of hydrophobicity. Methods: In order to improve efficacy and reduce toxicity, R848 and siCD47 were entrapped in amphiphilic PEG-PLGA nanoparticles by double emulsification and stable nanoparticles NP/R848/siCD47 were generated to investigate their anti-tumor effects in a TNBC tumor-bearing mouse model. Results: Here, we show that PEG-PLGA nanoparticles are effective nanocarriers that can safely and effectively deliver siCD47 and R848 to tumor tissue, as demonstrated by retarded tumor growth. Mechanistically, downregulation of CD47 expression and activation of DCs took part in promoting the immune response of cytotoxic T cells (CTLs). Meanwhile, a decrease of myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs) indicated the modulating of the tumor immune microenvironment. Discussion: To our best knowledge, our study pioneered co-delivery system for hydrophilic siCD47 and hydrophobic R848. It can maximize break tumor immune escape caused by CD47 and simultaneously enhance antigen presentation by activating DCs for effector T cell killing while regulating the tumor microenvironment as expected. Not only does it conform to the reports of previous basic research, but also it can break the bottleneck of their clinical application hopefully. Collectively, our findings could lay the foundation for future therapeutic strategies of TNBC.